Multi-channel transmitters for free-space optical communication systems - Paśnikowska, Aleksandra; Stopiński, Stanisław; Anders, Krzysztof; Rojewski, Mariusz; Kustosz, Łukasz; Piramidowicz, Ryszard (Photonics Letters of Poland, 2026)
This study presents a Free Space Optical Communication system using InP-based integrated transceivers, demonstrating multichannel transmission capabilities. The system utilizes photonic integrated circuits (PICs) to achieve compact, energy-efficient transceivers suitable for scalable optical communication applications. Successful multi-channel data transmission at rates of up to 10 Gb/s was achieved in both indoor (2 m) and outdoor (up to 10 m) environments. The design incorporates distributed Bragg reflector (DBR) lasers, electro-absorption modulators, and arrayed waveguide grating (AWG) multiplexers. The system showcases high-quality transmission with low bit-error rates (BER ≤ 10⁻¹¹) and minimal power penalties. Full Text: PDF References H. Kaushal and G. Kaddoum, "Optical Communication in Space: Challenges and Mitigation Techniques", IEEE Commun. Surv. Tutor. 19(1), 57 (2017) CrossRef C. Mathas, "Free-space optics restores communications after Sept. 11", Lightwave Online. accessed: Dec. 23, 2025. [Online]. DirectLink H. Hemmati, A. Biswas, I.B. Djordjevic, "Deep-Space Optical Communications: Future Perspectives and Applications", Proc. IEEE 99(11), 2020 (2011) CrossRef M.A. Fernandes, P.P. Monteiro, F.P. Guiomar, "Free-Space Terabit Optical Interconnects", J. Lightwave Tech., 40(5), 1519(2022) CrossRef H. Zhao et al.,"Indium Phosphide Photonic Integrated Circuits for Free Space Optical Links", IEEE J. Sel. Top. Quantum Electron. 24(6), 1 (2018) CrossRef G. Terrasanta, M.W. Ziarko, N. Bergamasco, M. Poot, J. Poliak, "Photonic Integrated Circuits for Optical Satellite Links: A Review of the Technology Status and Space Effects", Int. J. Satell. Commun. Netw. 43(3), 210 (2025), CrossRef L.A. Coldren et al., "High Performance InP-Based Photonic ICs—A Tutorial", J. Light. Technol. 29(4), 554 (2011) CrossRef A. Paśnikowska, S. Stopiński, A. Kaźmierczak, R. Piramidowicz, "Multi-Channel Integrated Transmitters With Cyclic AWG", J. Light. Technol. 42(7), 2371 (2024) CrossRef